Cytotoxicity and Isolation of Betullinic Acid from Anthonotha noldeae Stem Bark - Atiko, Rejoice; Kwaji, Andrew; Nyakuma, Bemgba B.; Pius, Philip; Umar, Ibrahim M.; Muhammad, Adam I.; Musba’u, Idriss Bamidele (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The cytotoxicity and isolation of betullinic acid from Anthonotha noldeae stem bark were examined in this study. The stem bark was extracted using methanol (MeOH) via the cold maceration technique. The MeOH produced a crude extract of 125.18 g (6.78%), which was further divided into n-hexane, dichloromethane (DCM), and ethyl acetate (EtOAc) fractions with yields of 10.23%, 11.74%, and 12.22%, respectively. Cytotoxicity assays using brine shrimp lethality tests revealed that the DCM and EtOAc fractions exhibited substantial concentration-dependent toxicity, achieving 100% mortality at 500–1000 ?g/mL. The LC50 values for the DCM and EtOAc fractions were 16.33 ?g/mL and 28.64 ?g/mL, respectively. Column chromatography of the fractions led to the isolation of the compound M1 (5 mg), characterized using FTIR, 1H NMR, and 13C NMR spectroscopy. FTIR analysis identified functional groups consistent with carboxylic acids and alkenes, while NMR spectroscopy confirmed the presence of six methyl groups, vinyl protons, hydroxyl groups, and carboxyl functionalities. The compound was identified as the bioactive triterpene known as betulinic acid. The findings provide novel insights into the phytochemistry of Anthonotha noldeae, highlighting its potential as a source of bioactive compounds and application in traditional medicine.